Adolescent Moral Development in Families - Ujang Dedih (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
This study aimed to investigate parents’ goals and objectives in fostering the moral values to their adolescents, parents’ moral values instilled toward their teenagers, parents’ approach and methods in instilling moral values, and parents’ guidance development in nurturing moral values toward adolescent. This research used descriptive-analytic method, and qualitative-naturalistic approach. It applied observation, interview and documentation. It investigated three families with a different education background. Findings show that family with undergraduate education background is relatively very good in fostering the values of Akhlak Karimah to their teenagers. Their success was supported by clear goals and objectives, consistent and continuous delivery of materials, the use of appropriate approaches and methods, and good and harmonious family. These factors contributed to excellent moral education for their teenager. Family with a high school education background applied moral education using the formulation of objectives, materials, and the arrangement of a family atmosphere but the result was less optimal because they used less precise methods and approaches. Family with a junior high school education background had not achieved a satisfactory result in moral education for their teenagers because they did not formulate well objectives, materials, methods, approaches and the arrangement of a family atmosphere